A Study on Data Storage Security Issues in Cloud Computing - Bnasod, Nayana; Dhore, Pranjal; Balani, Nisha (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing , a remote service platform used to store information and execute applications. It lets you run services and data online by request via a simple internet connection. Cloud computing is a relatively new technology that will become more widespread. The adoption of this technology is not without its challenges and risks. With the cloud model, you lose control over physical security. In a public cloud, you are sharing computing resources with other companies. In a shared pool outside the enterprise, you don’t have any knowledge or control of where the resources run. Exposing your data in an environment shared with other companies could give the government “reasonable cause” to seize your assets because another company has violated the law. Simply because you share the environment in the cloud, may put your data at risk of seizure. Storage services provided by one cloud vendor may be incompatible with another vendor’s services should you decide to move from one to the other. Vendors are known for creating what the hosting world calls “sticky services”—services that an end user may have difficulty transporting from one cloud vendor to another (e.g., Amazon’s “Simple Storage Service” [S3] is incompatible with IBM’s Blue Cloud, or Google, or Dell). This study aims to review and classify the issues that surround the implementation of cloud computing which a hot area that needs to be addressed by future research.